Impact of Palm Frond Particle Size on the Characteristics of Biodegradable Particleboard - Yudis Rahma Risky; Sunardi Sunardi; Shofiatul Ula; Iman Saefuloh; Yusvardi Yusuf; Agung Sudrajad; Saifudin Saifudin (Politeknik Manufaktur Negeri Bangka Belitung, 2026)
Particleboard is a composite material based on lignocellulose that can be produced from agricultural waste, serving as an alternative to traditional wood products. This study utilized waste from oil palm fronds and empty fruit bunches as raw materials for the production of particleboard. The oil palm fronds were processed into filler particles of varying sizes: 80-mesh, 60-mesh, and 35-mesh. The composition of the raw materials included 50% oil palm frond particles, 15% empty fruit bunch fiber, 20% PVAc adhesive, and 15% epoxy resin. The particleboard was manufactured using a single-punch cold-press process at a pressure of 0.30 MPa for 120 minutes, followed by curing at 150°C for 60 minutes. Various characteristics of the particleboard were tested, including density, water content, thickness swelling, modulus of rupture (MOR), and modulus of elasticity (MOE). The results indicated that the particle size of 80-mesh yielded the best properties, with a density of 0.88 g/cm³, a water content of 5.51.6%, thickness swelling of 1.13%, a MOR of 19.79 MPa, and a MOE of 1.08 GPa. All specimens met the standards set by SNI 03-2105-2006 for density, water content, thickness swelling, and MOR; however, the MOE value did not meet the required standards.